Evaluating student satisfaction - restricting lecturer professionalism: outcomes of using the UK national student survey questionnaire for internal student evaluation of teaching. Issue 3 (2nd April 2020) - Arthur, Linet
Abstract: In the neo-liberal context of a UK university, responding to student feedback in order to raise student satisfaction levels is important in improving National Student Survey (NSS) scores. This article focuses on the impact of a UK university's new student feedback questionnaire - for individual modules - which used the NSS questions. The research draws on survey data (N = 101) to identify lecturers' views and three student focus groups. The outcomes raised issues relating to performativity, professionalism and 'provision', the latter defined as the university's contract with each student, including the aspects that affect the student learning experience but are beyond the lecturers' control, for example, class sizes and timetables. The results indicate that by recognising the impact of provision university managers may be better able to develop systemic improvements to student experience and (in the UK) a corresponding uplift in NSS and Teaching Excellence Framework (TEF) results. The article puts forward a model linking performativity, professionalism and provision to the relationships between university managers, academics and students. This model could enrich understandings of professionalism and performativity, extend the range of issues affecting student experience in SETs and support data analysis in future research studies.